PERLINDUNGAN KHUSUS TERHADAP ANAK KORBAN KEJAHATAN SEKSUAL MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Astika Suriyani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThis research aims to determine the extent of the special protection granted by the government to the child victims of sexual crimes according to Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak, and to determine the factors that cause children vulnerable as victims of sexual crimes and what is impeding the efforts to provide protection especially to children as victims of sexual crimes.Authors to achieve these objectives using tecniques of data collection in the form of library research and field studies in the relevant agencies are Lembaga Pemasyarakatan Kelas IIA Samarinda, Komisi Perlindungan Anak Indonesia Daerah Samarinda and Polsekta Samarinda Ilir.Data children as victims of sexual crimes reported to the Komisi Perlindungan Anak Indonesia Daerah Samarinda as many 137 cases adn for offenders who are in Lembaga Pemasyarakatan Kelas IIA Samarinda there are 97 actors consisting of 8 child offenders and 89 adult offenders.Role Komisi Perlindungan Anak Indonesia Daerah Samarinda in accordance with Pasal 59 Ayat (1), which reads “government, local government and other state institutions are obliged and responsible to provide special protection to children”, among others, mentoring psychologist, set up safe houses. And for criminal sanctions for sexual offenders which is regulated in Pasal 81 Ayat (1) and (2) Undang-Undang Perlindungan Anak to a penalty of minimum 5 (five) years and maximum of 15 (fifteen) years with fine of Rp 5.000.000.000 (five billion rupiah).Children as victims of sexual crimes has not received adequate special protection because of several factors. Of the research is still much to be improved both on the infrastructure, legal standing Komisi Perlindungan Anak Indonesia Daerah Samarinda and understanding of society and the law enforcement will be the framework of child protection. So expect the government to improve and prepare including finding stake holder (authorities) on the way out how child victims of sexual crimes can be handled in rehabilition area.Keywords : children as victims of sexual crimes, child protection, and special protection to children vitims of sexual crimes